Search for the disappearance of muon antineutrinos in the NuMI neutrino beam - Adamson, P; Auty, D; Ayres, D; Backhouse, C; Barr, G; Bishai, M; Blake, A; Bock, G; Boehnlein, D; Bogert, D; Cao, S; Cavanaugh, S; et al. (2011)
We report constraints on antineutrino oscillation parameters that were obtained by using the two MINOS detectors to measure the 7% muon antineutrino component of the NuMI neutrino beam. In the Far Detector, we select 130 events in the charged-current muon antineutrino sample, compared to a prediction of 136.4±11.7(stat)-8.9+10.2(syst) events under the assumption |Δm̄2|=2.32×10-3eV2, sin2(2θ̄)=1.0. Assuming no oscillations occur at the Near Detector baseline, a fit to the two-flavor oscillation approximation constrains |Δm̄2|<3.37×10-3eV2 at the 90% confidence level with sin2(2θ̄)=1.0. © 2011 American Physical Society.